PATRIARCHAL PRACTICE AGAINST WOMAN CHARACTER’S IN PAT BARKER’S THE SILENCE OF THE GIRLS - Firdausiyah, Fira; Rahayu, Anik Cahyaning (TANDA, 2025)
Various cultural problems have existed from the past to the present life of society. One of them is patriarchal culture or patriarchal practice. Patriarchal practice can be known through various writings on social media and literary works. This article deals with patriarchal practice happening in a literary work, in this case, in a novel entitled The Silence of The Girls written by Pat Barker. The aims of the research are to describe the patriarchal practice portrayed in the novel and the women’s struggle to face the patriarchal practice done by the men. This novel tells about Briseis, the main character, and the other two woman characters, who experience domination and oppression from man characters. In conducting the research, Sylvia Walby's theory of patriarchy is employed. In addition, this study is designed by using a qualitative descriptive method that focuses on presenting data directly through observation. Besides, feminist literary criticism is applied because this study focuses on the issue of women's equality. The results of the study shows that men dominate by abusing their power. The men are more powerful than the women by controlling, oppressing mercilessly with violence and sexuality such as rape, without considering their throne as women. Therefore, the women cannot voice what they want to convey because their voices are rejected, and they do not have the right to speak out, which can result in losing their identity as women. However, Brises and the other women build a community and solidarity to strengthen them, so that they can survive in facing patriarchal practices by strengthening each other and giving the best support. Moreover, they can strengthen self-awareness to achieve prosperity and freedom. Those are women’s manner to be able to survive during the war and to face men’s domination.